Removal of pyrimethanil and fenhexamid from Saccharomyces cerevisiae liquid cultures - Bizaj, Etjen; Cus, Franc; Raspor, Peter (Food technology and biotechnology, 2011)
The capacity for the removal of pyrimethanil and fenhexamid, two fungicides commonly used for the control of Botrytis cinerea in vineyards, has been evaluated during an alcoholic fermentation process in batch system. Commercial and wild strains of Saccharomyces cerevisiae were used. Batch fermentations were carried out in yeast extract-malt extract medium (YM) with 18.0 % (by mass) glucose, and the fungicides were added separately at three concentrations: 0.1, 1.0 and 10.0 mg/L. The removal capacity of yeast strains was also examined in stationary phase cultures of Saccharomyces cerevisiae. Stationary assays were performed with yeast biomass harvested from the stationary phase of an anaerobic fermentation process, with separate additions of 0.1, 1.0 and 10.0 mg/L of both fungicides. Removal studies with stationary phase cells were performed with viable and non- viable cells inactivated with sodium azide. This study clearly shows that both Saccharomyces cerevisiae strains were able to remove fenhexamid and pyrimethanil in stationary and fermentative assays. The removal potential is shown to be strain dependent in stationary but not in fermentative assays. However, the removal potential is dependent on the type of fungicide in both stationary and fermentative assays. In stationary phase cultures no significant difference in fungicide removal potential between viable and non-viable cells was observed, indicating that both pesticides were not degraded by metabolically active cells. However, the presence of both pesticides influenced fermentation kinetics and only pyrimethanil at 10.0 mg/L increased the production of volatile acidity of both strains. Key words: alcoholic fermentation, S. cerevisiae, pyrimethanil, fenhexamid, synthetic media